PERLINDUNGAN HUKUM KREDITOR SEPARATIS TERHADAP JAMINAN KEBENDAAN PIHAK KETIGA DALAM PERKARA KEPAILITAN (STUDI KASUS PERKARA KEPAILITAN NOMOR : 21/PDT.SUS.GUGATAN LAIN-LAIN/2019/PN.NIAGA SBY., JUNCTO PERKARA NOMOR : 18/PDT.SUS/PKPU/2018/PN.SBY - Subagyo, Heri; I Made Kanthika (LPPM, Universitas Muhammadiyah Riau, 2023)
Creditors are classified into three categories, namely separatist creditors, preferred creditors, and concurrent creditors. This is different from the classification in general civil law, where creditors are only classified into two, namely preferred and concurrent creditors. Separatist Creditors, namely creditors whose receivables are guaranteed and bound by material guarantees such as Mortgage, Mortgage, Pledge and Fiduciary. Separatist creditors or Secure Creditors can exercise their rights based on the material guarantees they have as if no bankruptcy had occurred, in the case studied it was found that PT. Hardys Retailindo signed a Credit Agreement with Bank J. Trust Indonesia, on May 28, 2012 for Working Capital purposes, which is approximately IDR 140,000,000,000 (One Hundred Forty Billion Rupiah), in this case the Bank. J Trust as a separatist creditor whose debt is guaranteed should get legal and preliminary protection from bankrupt debtors, in this study discusses legal protection for separatist creditors